Organized Youth Sports Trajectories and Adult Health Outcomes: The Young Finns Study - Yang Xiaolin; Kukko Tuomas; Lounassalo Irinja; Kulmala Janne; Hakonen Harto; Rovio Suvi P; Pahkala Katja; Hirvensalo Mirja; Palomäki Sanna H; Hutri-Kähönen Nina; Raitakari Olli T; Tammelin Tuija H; et al. (Elsevier, 2026)
Introduction
This study identified the trajectories of organized youth sports over 9 years in youths aged 9–18 years and examined whether the trajectories predicted physical activity, sedentary behavior, and obesity in midlife.
Methods
Self-reported organized youth sports trajectories were identified for participants between 1980 and 1989 (N=3,474). Accelerometer-derived physical activity was quantified for participants (n=1,349) in 2018–2020. Sociodemographic, physical activity, and TV viewing data were collected through questionnaires either at baselines or follow-up. Adult BMI was calculated to clarify obesity. Associations of organized youth sports trajectories with adult physical activity, sedentary behavior, and obesity were evaluated using mixture models, which were stratified by sex and conducted in 2022.
Results
Three organized youth sports trajectories were identified for boys and girls (sustained high-sports participation, 12.0%/7.5%; sustained moderate-sports participation, 14.0%/13.3%; and low-sports/nonparticipation, 74.0%/79.2%). Boys sustaining both moderate- and high-sports participation had higher levels of adult self-reported physical activity (β=0.59, p=0.007; β=0.69, p<0.001) than low-sports/nonparticipating boys. Girls sustaining both moderate- and high-sports participation accumulated more total physical activity (β=113.4, p=0.009; β=144.3, p=0.002), moderate-to-vigorous physical activity (β=7.86, p=0.016; β=14.01, p<0.001), step counts (β=1,020, p=0.003; β=1,045, p=0.005), and self-reported physical activity (β=0.79, p<0001; β=0.63, p=0.003) in midlife than their low-sports/nonparticipating counterparts. Girls sustaining moderate-sports participation accumulated more light-intensity physical activity (β=19.79, p=0.012) and less sedentary time (β= −27.65, p=0.002), and those sustaining high-sports participation had lower obesity prevalence (OR=0.41, p=0.009) 40 years later than low-sports/nonparticipating girls.
Conclusions
Sustained participation in organized youth sports is independently predictive of physical activity patterns, sedentary time, and obesity in midlife, especially in girls, thus contributing to the development of a healthy and active lifestyle across the life course.